Study the Effect of Reverse Rotation Friction Stir Processing on the dissimilar aluminum alloys - Hameed, Ahmed M.; Resan, Kadhim K.; Eweed, Khalid M. (Al-Nahrain Journal for Engineering Sciences, 2017)
Friction stir welding (FSW), a solid-state welding process, it’s involve a welding by friction between two metals or alloys, and also using for the joining of dissimilar materials due to the lower processing temperature over conventional fusion welding, it's include only one pass of welding. Friction Stir Processing (FSP) is a recent outgrowth of the Friction Stir Welding (FSW) process and relies on solid-state deformation to modify the structure of the workpiece, it's involve two pass or more of welding and applied either on the base metal(BM) or to join the two alloys/metals. In this paper the new method used, namely reverse rotation friction stir processing (RFSP), this research aims to study the effect of (RFSP) technique on the mechanical properties of welded alloys. (FSW) includes a single pass of the welding line but the second method (RFSP) involves two pass of welding (forth and back) but the 1st pass with a rotation speed in clockwise and the 2nd pass in counter-clockwise. The alloys used of dissimilar AA 2024 and AA6061 aluminum alloys of (3mm) thickness, the parameters used in this research include different rotational speed (1600, 1800, 2000 and 2200) RPM and one feed speed (25) mm/min. In the tensile test the results of reverse rotation friction stir processing (RFSP) was higher than friction stir welding (FSW) for all rotation speeds of welding except (1800 RPM). In the microhardness measurement the values of hardness for all samples at the nugget zone is higher than the basemetal of 6061-T6 and lower than the basemetal of 2024-T3. The efficiency of ultimate tensile strength reaches to about (72 %) for (RFSP) as compare with value of (FSW) and it’s about (44%) at rotation speed (1600 RPM).The only exception of welding was when the rotational speed of (1800 RPM), where the (FSW) is better than (RFSP), efficiency was approximately (77%) for the (FSW) compared with the results of (71%) (RFSP).